Drug rash with eosinophilia and systemic symptoms syndrome, a uncommon but fatal illness, paediatricians should be aware of: a case of 13 year old female child - Behera, Jyoti Ranjan; Sahu, Sanjay Kumar; Gupta, Abhas (International Journal of Contemporary Pediatrics, 2020)
Drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is a fatal illness manifested by fever, morbilliform rash, multi systemic involvement and eosinophilic leucocytosis with about 10% mortality. Authors report DRESS syndrome in an adolescent girl due to anti-depressant and anti-psychotic which improved dramatically after withdrawal of offending drugs and starting of steroids